Marseille, une ville méditerranéenne entre pénurie et inondation - Martine Chalvet (Éditions en environnement VertigO, 2011)
Based on a interdisciplinary analyse crossing history and sociology, this paper analyses the relationship to water of the inhabitants and the decision makers of the Mediterranean French city of Marseilles, from the XIXth century to nowadays. The late XIXth century is characterised by a culture of water abundance, in a context of technical control responding to economic and demographic growths. However such urban growth gradually exposes the inhabitants to floods, caused by rivers’ overflows and storm runoff. Yet, those recurrent physical processes have not modified the previous culture of water abundance, based on modernistic view without any effective culture of integrated floods management.